La finesse du paysage - Franco Farinelli (Projets de Paysage)
In “The arguzia del paesaggio”, the article presented here in translation (which is part of an essay published in I segni del mondo, 1992) F. Farinelli presents a critical and a historico-philosophical analysis of the concept of landscape as it was developed in geographical sciences (particularly in the reflection of Humboldt) and as considered today (though the article was published in 1991) in the social sciences.